Korelasi Skor Lund-Mackay dan Volume Cairan Sinus Berdasarkan Gambaran CT-Scan Sinus Paranasalis 3D dengan Skor SNOT-22 pada Pasien RSK Tanpa dan dengan Polip - Muhammad Ridha Maulana; Nurlaily Idris; Nikmatia Latief; Burhanuddin Bahar; Muhammad Fadjar Perkasa; Muhammad Ilyas (Lembaga Penelitian Universitas YARSI, 2019)
The aim of this study is to determine the correlation between Lund-Mackay scores and sinus fluid volume based on 3D CT paranasal sinus scan with SNOT-22 score in patients with chronic rhinosinusitis without and with polyps. This research was conducted at the Department of Radiology Hasanuddin University Hospital Makassar from April to June 2019. Samples were 38 patients without and with polyps in age ? 18 years. The method used is the Spearman rho test. The results showed a correlation between sinus fluid volume and SNOT-22 score in patients with chronic rhinosinusitis without polyps n value 25, p value 0.042 (p less than 0.05), the higher the sinus fluid volume, means the SNOT-22 score was higher in patients with chronic rhinosinusitis without polyps. There was no correlation between sinus fluid volume and SNOT-22 score in patients with chronic rhinosinusitis with polyps n value 13, p value 0.077 (p less than 0.05), there was not any correlation between Lund-Mackay scores and SNOT-22 scores in patients with chronic rhinosinusitis without and with polyps.